Ultrasound-Guided Corticosteroid Injection in Patients with Carpal Tunnel Syndrome: Efficacy of Intra-Epineurial Injection - Hsu, Yi-Chih; Yang, Fu-Chi; Hsu, Hsian-He; Huang, Guo-Shu (Ultraschall in der Medizin - European Journal of Ultrasound, 2018)
Purpose To identify the ultrasound (US) findings of intra-epineurial corticosteroid injection during US-guided hydrodissection in patients with carpal tunnel syndrome (CTS), and to determine their clinical relevance in relation to treatment outcomes.Materials and Methods We performed 101 US-guided hydrodissections and corticosteroid injections in 101 patients with CTS, and evaluated their pre- and post-injection US findings. We categorized these injections into two groups based on the occurrence of intra-epineurial injection. We also recorded clinical data including sex, age, side of injection, BMI, and the duration of pre-injection CTS-related discomfort. The outcomes were measured using the Likert satisfaction scale and Boston Carpal Tunnel Questionnaire (BCTQ) scores. The clinical data, cross-sectional area of the median nerve (CSA-MN) at the inlet of the carpal tunnel measured on US images, and the symptom relief for the patients receiving intra-epineurial and extra-epineurial injection were compared.Results The intra-epineurial injection rate was 38.6 % in the 101 US-guided injections. The clinical data, pre-injection CSA-MN at the inlet of the carpal tunnel, and pre-injection BCTQ scores showed no significant intergroup differences (p > 0.05). The group with intra-epineurial injections had significantly decreased CSA-MN (difference in means, 2.5 mm2; p < 0.0001), greater patient satisfaction (p = 0.002), and lower BCTQ scores (p < 0.05) than the group with extra-epineurial injections.Conclusion We characterized the US findings of intra-epineurial corticosteroid injection during US-guided hydrodissection. Intra-epineurial injection provided a more meaningfully reduction in edema of the MN, greater patient satisfaction, and greater symptom relief than extra-epineurial injection.
Keywords: carpal tunnel syndrome; corticosteroid; epineurium; injection; ultrasound guidance